Prevalence of Anisakid Nematodes in Fish in China: A Systematic Review and Meta-Analysis - Liu, Qing; Wang, Qi; Jiang, Jing; Ma, Jun-Yang; Zhu, Xing-Quan; Gong, Qing-Long (Frontiers in Veterinary Science, 2022)
Anisakidosis, caused by anisakid larvae, is an important fish-borne zoonosis. This study aimed to summarize the prevalence of anisakid infection in fish in China. A systematic review and meta-analysis were performed using five bibliographic databases (PubMed, CNKI, ScienceDirect, WanFang, and VIP Chinese Journal Databases). A total of 40 articles related to anisakid infection in fish in China were finally included. Anisakid nematodes were prevalent in a wide range of fish species, and the overall pooled prevalence of anisakid nematodes in fish in China was 45.5%. Fresh fish had the highest prevalence rate (58.1%). The highest prevalence rate was observed in Eastern China (55.3%), and fish from East China Sea showed the highest prevalence of anisakid nematodes (76.8%). Subgroup analysis by sampling year suggested that the infection rate was higher during the years 2001-2011 (51.0%) than the other periods. Analysis of study quality revealed that the middle-quality studies reported the highest prevalence (59.9%). Compared with other seasons, winter had the highest prevalence (81.8%). The detection rate of anisakid nematodes in muscle was lower (7.8%, 95% CI: 0.0-37.6) than in other fish organs. Our findings suggested that anisakid infection was still common among fish in China. We recommend avoiding eating raw or undercooked fish. Region, site of infection, fish status and quality level were the main risk factors, and a continuous monitoring of anisakid infection in fish in China is needed.